Análise dinâmica das vigas sandwich comprimidas - Villaça, Sérgio Fernando (1970)
The problem undertaken is this work is to determine and analyze the equations of lateral vibrations of sandwich beams with an axial compressive load, as well as the analysis of the instability loads by a dynamic method. Some cases, corresponding to several boundary conditions, were studied and the respective frequency equations were established. The behavior of the natural frequencies with the variation of the compressive load is plotted for several values of the shear stiffness of the sandwich beams. Numerical tables give the results for each case of boundary conditions.